2021
DOI: 10.4317/jced.57798
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of face masks during the COVID-19 pandemic impact on oral hygiene habits, oral conditions, reasons to seek dental care and esthetic concerns?

Abstract: Background To evaluate the impact of the use of face masks on oral hygiene habits; oral conditions self-perception; reasons to seek dental treatment; and esthetic concerns. Material and Methods 1346 participants answered a web-based survey with questions related to the aims of the study. Descriptive statistic was performed and the responses were analyzed with chi-square test and regression analysis. Results With the use of masks, toothbrushin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 27 publications
3
20
2
1
Order By: Relevance
“…Thus, both null hypotheses must be rejected. Results are in line with previous studies which also found face masks to impact on self-perceived dry mouth [7,8] and halitosis [7,13,14]. Largest differences were observed between the items "mouth feels dry" and "lips feel dry", most probably as wearing face masks is likely to change the breathing pattern.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, both null hypotheses must be rejected. Results are in line with previous studies which also found face masks to impact on self-perceived dry mouth [7,8] and halitosis [7,13,14]. Largest differences were observed between the items "mouth feels dry" and "lips feel dry", most probably as wearing face masks is likely to change the breathing pattern.…”
Section: Discussionsupporting
confidence: 91%
“…This condition can decrease or worsen social communication. 26 Furthermore, 246 (24.4%) participants believed that wearing a mask diminished the beauty of their smile; specifically, 76.8% (189/246) of them were females (p ¼ 0.001). The result and the association with women are confirmed and can also be explained by a study concluded that women really missed looking at people's smile because of its importance in social relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pinzan-Vercelino et al noted that individuals had a lower frequency of tooth brushing and this was closely associated with an increased prevalence of halitosis. 26 Since the beginning of the pandemic period, there has been a change in eating habits. This has been due to various factors in particular stress and anxiety, greater sedentariness given by smart working, regulations that have reduced people's movements, and changes in the availability of food during the day.…”
Section: Discussionmentioning
confidence: 99%
“…Many of patients were seeking dental care in hospitals in the first months of the pandemic where many procedures were practiced according to the clinical practice guideline (Wu et al, 2021). In the literature, it was stated through a web-based survey that the patients are less concerned with their dental health, as they are still wearing masks, patients show less demand of the dental health care (Pinzan-Vercelino et al, 2021;Ribeiro et al, 2021). In the present study, it was found that 100% of the participants seek dental health care, however, the questionnaire was destinated for patients at dental office or dental clinic of a school.…”
Section: Discussionmentioning
confidence: 99%